2023
DOI: 10.1259/bjrcr.20220144
|View full text |Cite
|
Sign up to set email alerts
|

A case series of FDG PET scan: hypometabolic lesions that matter in oncology

Abstract: Interpretation of FDG PET images in oncology patients is in general a visual exercise of search for focal increased uptake (hypermetabolism). However, in some cases, hypometabolism (focal decreased uptake) can matter as much as hypermetabolism. We report three cases of FDG PET studies for oncological indications. All of them showed focal hypometabolic lesions suspicious of metastases. The diagnoses were then supported either by histological proof and/or follow-up imaging studies. The importance of being alert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In general, necrotic CRLM lesions are typically hypometabolic and hypodense and can hardly achieve satisfactory response [ 16 ]. That's why the temporarily responding segment II lesion has established the progression observed in the last two serial [ 18 F]FDG PET/CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…In general, necrotic CRLM lesions are typically hypometabolic and hypodense and can hardly achieve satisfactory response [ 16 ]. That's why the temporarily responding segment II lesion has established the progression observed in the last two serial [ 18 F]FDG PET/CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…For patients having received radiation therapy for brain metastases, either radiation necrosis or recurrent metastases can exhibit hypometabolism [30]. Patients with previous cerebrovascular accident, epilepsy, cerebral trauma, cerebral infection, other brain neoplasm or neurodegenerative diseases may also show asymmetrical hypometabolism [6]. It is therefore important to refer to relevant clinical history when hypometabolism is identified.…”
Section: Addressing Hypometabolism and Previous Studiesmentioning
confidence: 99%
“…Metastatic brain lesions may manifest as hypometabolism due to perifocal vasogenic oedema, cystic, necrotic, calcific or haemorrhagic components or inherent properties of tumour cells [6]. Zidan MA et al reported that 57.7% of brain metastases detected on FDG PET showed hypometabolism [26].…”
Section: Addressing Hypometabolism and Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation